Real-time polymerase chain reaction (RT-PCR) for the authentication of raw meats - Chung, H.H (Universiti Putra Malaysia, 2018)
Meat adulteration has been a signifcant issue in today’s food industry as it intertwine with religious, social and economic values. PCR based techniques for the detection of meat species in a meat admixture are primarily used by the industry as a reliable approach due to its sensitivity and reliability. This paper describes the design and verifcation of real-time polymerase chain reaction (RT-PCR) based assay for the detection of meat from various non- target species by using species specifc oligonucleotides. Five sets of species-specifc primers have been developed to target small regions (≤ 150 bp) of the mitochondrial D-loop. The specifcity, sensitivity and reliability of each assay have been verifed by using SYBR Green based RT-PCR. By using a cut-off CT of 30 cycles, all assays show sensitivity down to 0.05% of the DNA spike level. When applied to DNA templates from raw meat admixtures, assays were able to detect the target species up to a level of 0.1%. Hence, this verify the potential applicability of these assays in the meat industry.